Acupuncture as a Modality in Low Back Pain - Das TK; Ghatak RK (Indian Journal of Physical Medicine & Rehabilitation, 2008)
32 years married muslim female having chronic low back pain for four years was treated in the Deaprtmentof Physical Medicine, Burdwan Medical College, West Bengal in the year 2005. Patient could not tolerateNSAIDS due to recurrent peptic ulcer. Physiotherapeutic exercises and management with Ultrasonic therapyhad to be withdrawn due to nausea and vomiting reported by the patient. Patient was then put on Acupuncturetreatment. There was remarkable improvement with Acupuncture within 2 months. Exercise therapy andadvice regarding posture care was continued along with acupuncture therapy.